The poem of my Cid - Such, Peter, 1953- (Hispanic classics., 1987)
One of the most powerful and sustained works in all medieval literature, without which no series could be considered complete. The Poem of My Cid deals with the exploits of the medieval Castilian warrior, beginning with the sorrow of his departure into exile and focusing on his determination to regain the favour of his king. The poem is rich in incident and around the strength of the epic hero is developed the theme of the relationship between the individual and seigneurial society. The tribulations of his life and the drama of his battles against both Moors and Christians are presented with unusual directness and force. The translation preserves the tone of the original and reflects the vitality of its style while following the facing text closely. The full notes and the introduction cover problems of interpretation, style and background. Spanish text with facing-page translation, introduction and commentary.